2014
DOI: 10.4276/030802214x14044755581781
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study: Expanding the Concept of Play for Children with Severe Cerebral Palsy

Abstract: Introduction: Play is essential to a child's development, and is a dominating component of a child's life. Forming part of a broader study aiming to explore what parents of children with cerebral palsy understand by play, and its use in therapy and home programmes, this research article focuses on how parents expand their concept of play for their children. Method: A qualitative methodology and interpretive descriptive approach were taken. Following ethical approval, seven parents were recruited, completed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
0
12
0
9
Order By: Relevance
“…Play has been a widely discussed theme as a childhood occupation (Bartie et al, 2016;Graham et al, 2014;Fallon & MacCobb, 2013;Dionne & Martini, 2011). The results of this review indicate that play is the main occupation of children, as derived from the recognition of occupational therapists of the key role of play in childhood.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Play has been a widely discussed theme as a childhood occupation (Bartie et al, 2016;Graham et al, 2014;Fallon & MacCobb, 2013;Dionne & Martini, 2011). The results of this review indicate that play is the main occupation of children, as derived from the recognition of occupational therapists of the key role of play in childhood.…”
Section: Discussionmentioning
confidence: 91%
“…The research by Graham et al (2014) aimed to explore what the parents of children with cerebral palsy mean by playing and using it as a resource in therapy and at home. Based on a qualitative, interpretative and descriptive approach, 7 (seven) families of children with Cerebral Palsy (CP) were interviewed to understand the understanding of playing with their relatives.…”
Section: Resultsmentioning
confidence: 99%
“…In the light of the World Health Organization, 2007 International Classification of Functioning–Version Children and Youth (ICF–CY), the promotion of play and playfulness for children with disabilities can be approached by intervening on two areas: on personal factors, for instance sustaining motivation (Tatla et al, 2013), or on environmental factors, i.e., by improving parents’ conceptualization of play and teaching them how to effectively deal with play interactions (Okimoto et al, 2000; Graham et al, 2014), or by acting on the environment, by adapting toys and play situations (Hsieh, 2008). …”
Section: Mainstream Robotic Toys To Support Play and Playfulnessmentioning
confidence: 99%
“…Including more participants with disabilities could have rendered richer descriptions and a wider variety of occupations within the different categories, and is suggested for future research. Also, findings by Graham et al (2014Graham et al ( , 2015 described how children with cerebral palsy (CP) participated in leisure occupations in a different way than other children, but with equal enjoyment. That raises a question for future research on how their participation differs, and how participation and enjoyment correlate, based on experience.…”
Section: Limitationsmentioning
confidence: 99%
“…In relation to children's and adolescents' experiences of occupation, themes based on different types of play typical of children have been identified (Graham, Truman, & Holgate, 2014, 2015, as well as chores or school work, characterized as something serious, with rules, an expected outcome and requiring concentration (Larson, 2004). Asbjørnslett, Engelsrud, and Helseth's (2015) experiential study of children with disabilities found that three kinds of occupations had meaning for their transition during childhood, including building an identity.…”
mentioning
confidence: 99%